Future scenarios (projections to 2050) - Dorosh, Paul A.; Comstock, Andrew R. (International Food Policy Research Institute, 2019)
The Bangladesh fish sector has experienced both rapid growth and rapid change over the past several decades. With plentiful waterways, access to the sea, and a subtropical climate, prospects for future production growth are equally bright. Domestic demand for fish products is also increasing as rising incomes and more efficient value chains make fish products more accessible and affordable for both rural and urban households. How fast supply grows relative to demand will determine not only future movements in real prices of fish products but also the feasibility of significant levels of exports. Our analysis of future production trends involves modeling different growth rates of the various fish production systems: inland capture, aquaculture, and marine fisheries. Aquaculture development has recently been stressed by both private and public sector organizations (FAO 2014). Indeed, aquaculture productivity has increased, although this has not been the case for other fishery systems such as inland capture and marine fisheries. All these systems are beset with their own constraints, but each have unique opportunities to contribute to future growth.